AKSELERASI PENETAPAN STANDAR KOMPETENSI SUMBER DAYA MANUSIA (SDM) KEPARIWISATAAN UNTUK MENGHADAPI ERA MEA YANG SEDANG BERGULIR - I Made Darsana; Nyoman Surya Wijaya (Jurnal Ilmiah Hospitality Management, 2016)
Tourism has very important role to face AEC era, which began in 2015. Indonesia has had an agreement to ratify the globalization of labor markets through the WTO since 1994 and in 1999 declared himself in G20 membership. Many foreign investors invest their shares in Bali, it makes local people less motivated to open the field of employment. It urged a challenge for tourism human resourcse in Bali. Certification of competence for tourism human resources to face AEC is very important and essential. Tourism competency certification program that has been created by the government should be utilized maximally either by assessors in tourism or tourism human resources in Bali. The position of top managers at star-rated hotels in Bali which has been widely taken by foreign human resources, will be taken over by local tourism human resources in Baliwhich have the compentecy certification. It will be happened if the human resorces competency meets the criteria of competence that requisited by the management.